Assessment of Right Ventricular Systolic Dysfunction Using 2D STE to Predict Short Term Outcome in Patients with Heart Failure with Reduced Ejection Fraction - Hasan, Md. Rakibul; Haque, Tuhin; Islam, Nurul; Asifudduza, Md.; Faysal, Md. Owashak; Quadir, Rahatul; Ali, Sharmin; Sonia, Hosne Ara (Cardiology and Cardiovascular Medicine, 2023)
Backgraound and Objectives: Right ventricular functional assessment is challenging using conventional methods due to its complex geometry. Speckle tracking imaging using 2D is a novel method for assessing right ventricular systolic function in heart failure patients. The aim of this study was to predict short term outcome by RVFWS using 2D speckle tracking echocardiography in patients with heart failure with reduced ejection fraction. Methods: This Prospective Cohort Study was conducted in the Department of Cardiology, National Heart Foundation Hospital and Research Institute from April, 2019 to May, 2020. A total of 115 patients with heart failure with reduced ejection fraction were included after considering inclusion and exclusion criteria who underwent right ventricle function assessment using 2D STE .The patients were divided into two group according to RVFWS, In group 1,Normal Right ventricular systolic function ( RVFWS ≤ -19), In group 2, Abnormal Right ventricular systolic function (RVFWS >-19).Outcome were recorded after 6 months over telephone. Baseline characteristics, LVEF, TAPSE, PASP, RVGLS and outcome were compared between the two groups. Results: RVFWS was obtained successfully in 115 patients. Adverse short term outcome was more common in abnormal RVFWS group. RVFWS was found to be a best independent predictor of worst prognosis, compared with other echo parameters. ROC curve and Area Under ROC curve demonstrated that RVFWS could effectively predict short term outcome in patients with heart failure with reduced ejection fraction (Area under ROC curve was 0.7360, 95% CI = 0.631-0.840, P value <0.001). According to ROC curve analysis, RVFWS - 17.00 % appeared to be a good cutoff value for predicting short term outcome in patients with heart failure with reduced ejection fraction (Sensitivity 79.3%, Specificity 65.1% & Accuracy 68.7%). Conclusion: Abnormal Right ventricular free wall strain using 2D speckle tracing echocardiography was found to be a predictor of adverse short term outcome in patients with heart failure with reduced ejection fraction with good degree of sensitivity and specificity.